2013
DOI: 10.1109/tie.2012.2193861
|View full text |Cite
|
Sign up to set email alerts
|

A New Intelligent Fuzzy Controller for Nonlinear Hysteretic Electronic Throttle in Modern Intelligent Automobiles

Abstract: In order to control the nonlinear hysteretic electronic throttle adopted in modern automobiles, a new result for the tracking control of nonlinear hysteretic system is first proposed in this paper. Therefore we can realize the intelligent fuzzy logic controller in a well-behaved and systematic manner. A new closed-loop Back-propagation tuning is also proposed for the tuning of the fuzzy output membership functions to yield better tracking result. Finally, the controller synthesis is performed in a real-time en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The structure of FLS is a Mamdani type with a typical 'If-Then' rule and logical connectives to establish relations between the variables defined for the model of the system structure [1,4,10]. The fuzzy rules serve as an interface amongst qualitative variables in the model and the input and output numerical variables.…”
Section: To Find Real Surge Boundaries Via Fuzzy Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of FLS is a Mamdani type with a typical 'If-Then' rule and logical connectives to establish relations between the variables defined for the model of the system structure [1,4,10]. The fuzzy rules serve as an interface amongst qualitative variables in the model and the input and output numerical variables.…”
Section: To Find Real Surge Boundaries Via Fuzzy Reasoningmentioning
confidence: 99%
“…Today's automobiles have been shifted from a pure mechanical type to an electro-mechanical implementation [1][2][3][4][5]. Advanced technology has allowed turbo charger engine to improve vehicle performance as well as fuelefficient abilities that reduces carbon dioxide emission.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yuan et al 17,18 presented a self-learning controller for the ET valve based on neural network, for which strong robustness was achieved. Furthermore, to handle the nonlinear hysteretic behavior of ET, Wang and Huang 19 proposed an intelligent fuzzy control approach with feedforward closed-loop structure, wherein the fuzzy membership function was elegantly tuned with a novel closed-loop backpropagation (BP) method to achieve better tracking performance. However, the feedforward controller could not compensate nonlinear hysteresis (NH) accurately as the designed fuzzy rules were too simple.…”
Section: Introductionmentioning
confidence: 99%
“…However, the BP algorithm leads to slow training and also results in a local minimum. Wang et al [27] suggested an intelligent fuzzy controller with feedforward closed-loop configuration to deal with the nonlinear hysteretic behavior of ET. They also proposed a new closed-loop back-propagation tuning for the fuzzy output membership function to obtain better tracking performance.…”
mentioning
confidence: 99%
“…The study contributions are as follows. First, in the ET controller design, many previous studies [10], [14], [18]- [22], [25]- [27] treat only the throttle opening angle error as feedback, and do not consider the throttle opening angle change error. To the best of our knowledge, this study is the first to consider both the throttle opening angle error and the throttle opening angle change error as feedback.…”
mentioning
confidence: 99%